THE EFFECT OF TRAINING AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT THE REGENCY OF THE REGENCY OF MAJENE DPRD SECRETARIAT OFFICE - Sahur, M Ramli (Jurnal Ekonomi Balance, 2019)
This study aims to determine 1) the effect of training on employee performance at the Majene Regency DPRD Secretariat office, 2) the effect of job satisfaction on the Majene Regency DPRD Secretariat office and 3) the more dominant variables affect the Majene Regency DPRD Secretariat office. This research was carried out from January 2020 to March 2020 at the Majene Regency DPRD Secretariat office. This type of research used a quantitative approach. With a sample of 45 employees. The data analysis technique used is Validity Test, Reliability Test and Multiple Linear Regression Analysis. The results of the study are 1) Training has an effect on Employee Performance at the Majene Regency DPRD Secretariat Office, 2) Job Satisfaction has an effect on Employee Performance at the Majene Regency DPRD Secretariat Office and 3) of the two variables above Training and Job Satisfaction, Job Satisfaction is the more influential variable. on Employee Performance. Because Job Satisfaction has a greater tcount than the tcount of Training